Cultural Exchange Project between the University of Quindío and the University of Antioquia: Space of immersion in French as a Foreign Language - Loaiza Villalba, Neira; Colorado López, Doris (Íkala, Revista de Lenguaje y Cultura, 2014)
In this methodological article, we analyze the effects of an immersion activity on the cultural and communicative competence of a group of Colombian students from Universidad del Quindío and Universidad de Antioquia who learn French as a foreign language and who have an intermediate level of French. This academic and cultural exchange project is based on cooperative learning and project work. We carried out two guided tours in the department of Quindío and in the city of Medellin. Our results are based on the analysis we made of a questionnaire students answered, the evaluations they wrote about the project, the texts they produced and our reflections as teachers. The results demonstrate that learning becomes more meaningful in contexts where language favors both the access to linguistic and academic content and the creation of human, social and cultural links. This project strengthened the students' communicative and cultural competence but also their abilities for using technology and communication tools.